On The Term Vipulatva Found In The Mahābhārata - Dipak Jadhav (Institut Hindu Dharma Negeri Denpasar, 2020)
The Mahābhārata, one of the two major epics of ancient India, refers to the data for C, d, and t of each of the Svarbhānu, the Moon and the Sun where C is circumference (pariṇāha), d is diameter (viṣkambha), and nothing is clear about t. So far t has not been interpreted by any modern scholar. The terms used for t in the Mahābhārata are vipulatā, vipulatva,and viṣkambha, each of which means is largeness, extent, or width. This paper aims at igniting the process of interpreting t. It shows that t is rectilinear and cannot be interpreted in the manner in which the body of the Svarbhānu, the Moon or the Sun be proved to be cylinder or ellipsoid or spherical segment or oblate spheroid or disk. That t is a range of extent to d is, although reasonable and feasible, not fully acceptable as the ratio between d and t is not the same for the data given for d and t in the case of each of the Svarbhānu, the Moon and the Sun. t can be conjectured to have been prevalent till x where 500 BCE ≤ x ≤ 500 CE. x may go even beyond 500 BCE.